THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING CONTROLLING AND ITS IMPACT ON INVESTMENT MANAGEMENT: SYSTEMATIC LITERATURE REVIEW - Abbas Hameed Haider Al-Moussawi; Prof. Dr. Faez Abdulhasn Jasim Al_ Lami; Assist. Prof. Reyath Thea Azeez (Scholars Digest Publishing, 2025)
In light of the rapid development of technology, institutions benefit from the capabilities of advanced technologies to achieve efficiency. In a similar approach, control will benefit from artificial intelligence by providing great strategic supervision and reducing manual procedures, and providing a smart control service supported by modern technologies to improve investment management and thus achieve sustainable success in investment projects. The aim of the review is to fill the research gap by providing a blueprint for research methods on the topic in the literature and proposing a new intensive framework for the effective use of artificial intelligence, which represents modern technology has radically transformed investment project management, and artificial intelligence provides a wide range of opportunities to improve the efficiency and quality of investment management such as (data analysis, improved planning, improved decision-making). This paper includes a systematic literature review (SLR) approach and aims to shed light on the state of research on the use of artificial intelligence in enhancing control and the reflection of this development on investment management in projects to provide insights to scholars and researchers on this issue, and to reveal the implications of new artificial intelligence technology. This work makes significant contributions to guiding future research directions and developing theoretical foundations for the field of artificial intelligence. At the practical level, the work will help evaluate and understand the potential advantages and risks of applying artificial intelligence within the framework of control in institutions.
Keywords: Artificial Intelligence, Control, Investment.